Long COVID and its association with neurodegenerative diseases: pathogenesis, neuroimaging, and treatment - Zhao, Jinyang; Xia, Fan; Jiao, Xue; Lyu, Xiaohong (Frontiers in Neurology, 2024)
Corona Virus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has presented unprecedented challenges to the world. Changes after acute COVID-19 have had a significant impact on patients with neurodegenerative diseases. This study aims to explore the mechanism of neurodegenerative diseases by examining the main pathways of central nervous system infection of SARS-CoV-2. Research has indicated that chronic inflammation and abnormal immune response are the primary factors leading to neuronal damage and long-term consequences of COVID-19. In some COVID-19 patients, the concurrent inflammatory response leads to increased release of pro-inflammatory cytokines, which may significantly impact the prognosis. Molecular imaging can accurately assess the severity of neurodegenerative diseases in patients with COVID-19 after the acute phase. Furthermore, the use of FDG-PET is advocated to quantify the relationship between neuroinflammation and psychiatric and cognitive symptoms in patients who have recovered from COVID-19. Future development should focus on aggressive post-infection control of inflammation and the development of targeted therapies that target ACE2 receptors, ERK1/2, and Ca2+.